Efektivitas Sistem Informasi Kearsipan Dinamis Terintegrasi (SRIKANDI) Dalam Meningkatkan Indeks Pengawasan Kearsipan Pada Perpustakaan Dan Kearsipan Kabupaten Sinjai - Hainul, Hainul; Syamsuddin; Sani, Kiki Rasmala; Fitriani; Suardi Mukhlis (Program Studi Administrasi Publik, 2025)
This study aims to determine the effectiveness of the implementation of the Integrated Dynamic Archival Information System (SRIKANDI) in improving the archival oversight index at the Library and Archives Service of Sinjai Regency. The background of this study is based on the importance of archive digitization as part of bureaucratic reform and the realization of an electronic-based government system (SPBE). This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The effectiveness analysis refers to four indicators according to Sutrisno, namely: program understanding, on-target, on-time, and real change. The results show that the implementation of the SRIKANDI application has made a positive contribution to the order, efficiency, and accountability of archive management within the agency. However, several obstacles remain, such as network limitations, lack of technical training, and not all OPDs have used this system optimally. In addition, the use of manual letters is still found, especially from external parties such as student organizations and non-governmental agencies that have not been integrated into the SRIKANDI system. In conclusion, the implementation of SRIKANDI is considered effective in improving the archival oversight index, although its implementation still requires optimization, both from a technical and human resource perspective.